Pengembangan Media Pembelajaran Smart Apps Creator pada Materi Perkalian dan Pembagian Bilangan Desimal di Sekolah Dasar - Handayuni, Dea; Zainil, Melva; Amini, Risda (Universitas Negeri Padang, 2023)
This research was conducted due to the lack of optimal use of instructional media in elementary mathematics. The purpose of the research is to make learning media and assess the usefulness and validity of the resulting media. Media Smart Apps Creator is used in grade IV elementary school mathematics for multiplication and division of decimal numbers. Development (R&D) with the ADDIE model is this type of research. The steps of the research process in the ADDIE model include analysis, design, development, implementation and evaluation. Learning media is validated by a team of experts assessing educational materials by completing surveys including responses from teachers and students. The results of the material, media and language expert validation questionnaire on learning media with a very valid category score of 93,21%. Based on the teacher’s questionnaire at the research school, namely 98,33% and student responses, namely 95,04%, got a high score. Thus the Smart Apps Creator learning media in mathematics is able to help students in learning.